Non-tradition as factor of creativity in Portuguese typography - Curralo, Ana Filomena (2019)
Our purpose is to present a diachronic and synchronic overview of typeface design in Portugal, since the dawn of typography until current digital typeface design. This article also aims to contextualize typeface design main periods within the European typographic tradition. Our findings suggest that foreign expertise and aesthetics were frequently introduced in Portugal. By the opposite, other European countries were traditionally innovative in typeface design. There were in fact surges of innovation made in Portugal, but usually by the hands of foreigners working in Portugal. We address the Portuguese case in a global context of typeface design production. Along the history of typography until the Digital Revolution there were no outstanding singularities regarding foreign counterparts. However, the Digital Revolution brought a paradigm shift, with Portuguese designers gaining international prominence. Our results indicate that typefaces always relied on difference and on local / global interdependence. Tradition in typeface design was found non-linear and non-stationary. Instead, it was identified as an open, ever-changing process.